Phenotype, genotype, and mating type determination in oral Candida albicans isolates from pediatric patients with neutropenia. Issue 9 (16th August 2022) - Jafarian, Hadis; Gharaghani, Maral; Asnafi, Ali Amin; Hardani, Amir Kamal; Zarei‐Mahmoudabadi, Ali
Abstract: Background: The most frequent species of Candida to infect and colonize patients with neutropenia is still Candida albicans . This study aimed to provide detailed information on the phenotype, genotype, and mating type of oral C. albicans isolated from neutropenic pediatric patients, and to investigate how these characteristics are related. Methods: Two hundred fifty‐four oral samples from patients under 18 years old with neutropenia and malignancies were collected from January to October 2021. Samples were cultured on CHROMagar Candida . Isolates of C. albicans were identified with the germ tube test, chlamydospore production on cornmeal agar, and PCR‐RFLP. Genotyping of C. albicans isolates was carried out by amplifying the 25S rDNA gene with specific CAINT‐L and CA‐INT‐R primers. MTL a1 and MTL α1 primers were used to identify each mating type. Yeast peptone dextrose supplemented with phloxine B was used to identify different phenotypes. Results: Ninety‐two (36%) patients were positive for C. albicans . The mean age of patients was 7.85. Fifty‐three (58.9%) isolates demonstrated type A, 15 (16.7%) type B, 15 (16.7%) types D/E, and 7 (7.7%) type C. Three isolates each (3.3%) were homozygous for MTL a or homozygous for MTLα . All of the MTL ‐homozygous isolates were genotype A. There was a significant correlation between patients' underlying disease and genotype ( p  = 0.036). There was a significant correlation between mating type and genotype ( p  = 0.000). Conclusion: Most of the isolates exhibited a white phenotype, noted in the literature as the most virulent. Moreover, heterozygous strains were frequent and may play a role in Candida colonization. Abstract : The present study provides the detailed characterizations of phenotype, genotype, and mating type of oral C. albicans isolates from neutropenic pediatric patients. Although in previous studies, oral carriage was contained the least frequently genotype D of C. albicans, a higher frequency of genotype D (16.7%) was observed in our study. Moreover, the mating type of C. albicans was evaluated for the first time in clinical isolates from neutropenic patients.